The effect of the rehydration on seed germination of açaí (Euterpe oleraceae Mart.) - Souza, Patrícia Aparecida de (2018)
The açaí (Euterpe oleraceae Mart.) is abundant in riparian forest of pluvial forest from the Amazonian region and is frequently associated with degraded environments of secondary vegetation. The objective of this work was to evaluate the effect of rehydration of açaí seeds, aiming to speed up and create uniform patterns for the seed germination. The experimental design used was random blocks with six treatments (rehydration by soaking the seeds in water for 0 (T1), 3 (T2), 6 (T3), 9 (T4), 12 (T5) or 15 (T6) days), with seven repetitions of 25 seeds each. The seeds were sown soon after the rehydration process. Germination was evaluated every 10 days by counting the germinated seeds. The averages were compared with the Scott-Knott test to the level of 5% probability. The results showed significant differences among the control (T1) and the others periods of rehydration (T4>T6>T5>T2>T3), which did not show significant differences among them. The results showed that the rehydration process favored seedlings production, as it provided a higher percentage of açaí seed germination. The pre-treatment of rehydration accelerated the germination of the seeds; and the best rehydration period was 9 days, because it presented a higher seedling emergence rate index (IVE), in addition to the shorter time required to conduct the pre-treatment.